2020
DOI: 10.1111/ijcp.13800
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Sarcopenia in Hypertension: STAR and ACE Inhibitors Excel

Abstract: Background Hypertension and sarcopenia are commonly seen in older adults. The renin‐angiotensin system and the therapeutic use of angiotensin‐converting enzyme (ACE) inhibitors have been on the agenda of sarcopenia in different perspectives. Our aim was to explore the frequency of sarcopenia in patients with hypertension and to investigate the association between the use of ACE inhibitors and sarcopenia. Methods A total of 272 community‐dwelling adults were recruited. Anterior thigh muscle thickness was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…A similar controversy has also surrounded other molecules related to muscle function that have been proposed as biomarkers for frailty such as myostatin [47][48][49][50][51], follistatin [48,[50][51][52], and renin-angiotensin system elements [53][54][55][56][57]. Some authors have proposed that myostatin may act as a chalone, by turns restraining skeletal muscle growth in response to unfavorable metabolic scenarios or decreasing its own activity, when there is no need to restrain growth [50,51,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar controversy has also surrounded other molecules related to muscle function that have been proposed as biomarkers for frailty such as myostatin [47][48][49][50][51], follistatin [48,[50][51][52], and renin-angiotensin system elements [53][54][55][56][57]. Some authors have proposed that myostatin may act as a chalone, by turns restraining skeletal muscle growth in response to unfavorable metabolic scenarios or decreasing its own activity, when there is no need to restrain growth [50,51,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Picca et al [68] have described a U-shaped association between mTOR and cognitive function along the aging process. Thus, it may be that the seemingly contradictory results regarding certain putative molecular biomarkers of frailty are due to the up-regulation of compensatory systems on the frail organism, resulting in a U-shaped association; that is, during aging process, the serum concentration of such molecules is affected in one sense (increasing or decreasing), but later, the organism's compensatory mechanisms provoke the opposite effects (decreasing or increasing, respectively) [47,48,[50][51][52][53][54][55][56][57]. This is merely a general hypothesis that must to be confirmed for each molecule proposed as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is more frequently presented in hypertensive patients than in normotensive adults (32.2 vs. 7.8%) [2]. Additionally, hypertension independently increases the risk of sarcopenia more than 6.5 times more than normal blood pressure [2].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is more frequently presented in hypertensive patients than in normotensive adults (32.2 vs. 7.8%) [2]. Additionally, hypertension independently increases the risk of sarcopenia more than 6.5 times more than normal blood pressure [2]. Many studies have shown that RAS is possibly the main commonality between the pathophysiology of sarcopenia and hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation